Jon Krakauer's adventure on Mt. Everest - Werther, Scott P. (New York : Children's Press, 2002)
Relates the 1996 experiences of Jon Krakauer, a writer for Outside magazine, as he joined a group attempting to climb to the highest point on earth, the summit of Mt. Everest.
Includes bibliographical references (p. 44) and index.
Keywords: Krakauer, Jon. -- Juvenile literature; Krakauer, Jon; Mountaineering expeditions -- Everest, Mount (China and Nepal) -- Juvenile literature; Mountaineering accidents -- Everest, Mount (China and Nepal) -- Juvenile literature; Mountaineering -- Everest, Mount (China and Nepal); Everest, Mount (China and Nepal)